Memperkuat Komitmen Kerja Melalui Peran Kepemimpinan, Pemberian Motivasi, dan Peningkatan Kompetensi - Sugiarti (AKADEMIK: Jurnal Mahasiswa Ekonomi & Bisnis, 2021)
This study aimed to analyze and prove the influence of leadership and competence on work motivation and its implication toward employee’s commitment of technology agency research and application, both partially and simultaneously. The method used in this research were descriptive, survey and explanatory method with population size of 1.057 and sample size of 213 respondents. The method used to analysis data was SEM (Structural Equation Modeling). The research result, obtained the findings as follows: The Leadership and competence both partially and simultaneously had positive and significant impact on work motivation with contribution (R2) 51%. Partially leadership dominantly influence on work motivation. Further on Structural 2 showed, The leadership, competence and work motivation both partially and simultaneously had positive and significant impact on employee’s performance with contribution (R2) 78%. Viewed as partial, competence had dominantly toward employee’s commitment. Concerning on direct and indirect effect that work motivation was being partial mediating. This study found and recommended that to increase employee’s commitment of technology agency research and application needed to be extending work motivation, reflected by the dimensions of affiliation which supported with an increase in competence which reflected by the dimensions of attitude, and rectified the leadership which reflected by the dimensions of supporting.